E0 TRANSITIONS IN THE MID-SHELL EVEN-EVEN XE NUCLIDES - DECAY OF 31-S CS-124 TO LEVELS OF XE-124 - Walters, W; Rikovska, J; Stone, N; Shaw, T; Walker, P; Grant, I (Kluwer Academic Publishers, 1988)
The results of measurement of the gamma-ray and conversion-electron singles and coincidence spectra from the decay of 31-s124Cs to levels of124Xe are reported. Previously unobserved E0 transitions are identified and the X factors associated with their decay deduced. These results are discussed along with results of measurements on the structure of adjacent Xe nuclides © 1998 J.C. Baltzer A.G., Scientific Publishing Company.